Associate Nurse Unit Manager Clinical Leadership Programme: A Quasi‐Experimental Repeated‐Measures Study - Rebecca J. Jarden; Naomi Brockenshire; Nonie Rickard; Karan Sharma; Jessica Walters; Francis McNamara; Bianca Blatchford; Monika Drew; Bernadette Twomey; Meei Yann Loke; Helena Bujalka (Journal of Advanced Nursing, 2026)
ABSTRACT Aim To investigate the impact of a workplace leadership development programme on nurse manager leadership capability, knowledge, skills and confidence. Design Quasi‐experimental repeated‐measures design without a control group. Methods Associate Nurse Unit Managers at a large tertiary hospital in Melbourne, Australia, were invited to engage in a clinical leadership programme involving education and subsequent peer group reflective practice. A longitudinal survey with multiple pre‐ and post‐programme timepoints was conducted. Measures included the Leader Efficacy Questionnaire, researcher‐developed Likert‐scale items to evaluate programme learning outcomes and free response items. Quantitative items were analysed using descriptive statistics and repeated measures analyses; free response items were explored using content analysis. Results At baseline ( T 1), 103 Associate Nurse Unit Managers pooled from three cohorts consented to participate, of whom 98 provided sufficient data for analysis. Data were collected across 5 timepoints ( T 1– T 5); T 2 was used primarily to assess baseline comparability with T 1; longitudinal analyses focused on T 1, T 3, T 4 and T 5. Sixteen participants provided data at all relevant follow‐up timepoints and were included in the main longitudinal analyses. Following the leadership programme scores on the Leadership Efficacy Scale increased significantly. There were no significant changes in perceptions of organisational support or confidence in giving and receiving feedback. Participants reported positive experiences of the programme and identified future opportunities to refine topics, teaching and learning approaches and opportunities for peer networking. Conclusions A workplace clinical leadership programme for Associate Nurse Unit Managers demonstrated sustained increased leadership efficacy. Embedding coaching, mentoring and peer networks within leadership development may be an effective strategy to translate learning to practice and foster a sustainable healthy work environment. Further evaluation of education translation to practice and long‐term organisational outcomes are important next steps. Implications for the Profession For Associate Nurse Unit Managers, supporting leadership education by establishing organisation‐wide peer groups and structured coaching and mentoring may help consolidate and embed leadership knowledge and skills into practice. Future leadership education programmes should intentionally combine workplace learning with mentoring, organisational supports and peer networks to provide ongoing feedback and protected time, maximising long‐term benefits for staff wellbeing, retention and patient outcomes. Impact Effective clinical leadership is essential to nurse wellbeing and retention; however, the role preparation of these clinical leaders is variable and at times absent. A workplace leadership programme integrating education and peer‐group reflective practice for Associate Nurse Unit Managers produced measurable increases in leadership efficacy, strengthening frontline leadership capability. Embedding coaching, mentoring and peer networks into these programmes underpins future translation of learning into practice to build health work environments that promote staff wellbeing and patient safety. Reporting Method Transparent Reporting of Evaluations with Non‐randomised Designs (TREND). No Patient or Public Contribution No patients, service users, caregivers or members of the public were involved in this study. Instead, this study was focused on the experiences and perceptions of nurses.